A phenomenological study of the racial sensemaking of Chinese international doctoral students in the United States during and post the COVID-19 pandemic - Wang, Peiwen (International Journal of Qualitative Studies in Education, 2025)
Keywords: China; Ethnography; Interpretative phenomenological analysis; Pandemic; Phenomenology (philosophy); Qualitative research; Racism; Semi-structured interview; Sensemaking; dept.cur

Disconnected in a connected world: improving digital literacies instruction to reconnect with each other, ideas, and texts - Marangell, Joseph; Randall, Régine (Education Sciences, 2025)
This commentary addresses a problem of practice related to student disengagement in technology-rich classrooms, where learners are digitally connected but socially and academically disconnected. Although not an empirical study, the commentary draws on instructional examples from secondary- and graduate-level teaching. The authors examine how digital literacy instruction can strengthen engagement, reading comprehension, and ethical participation in online environments. The article highlights strategies such as the workshop model, multimodal composition, digital content curation, and the use of mentor texts to support critical thinking and collaborative learning. These practices aim to develop students’ analytical skills, awareness of audience, and recognition of their own positionality in digital spaces. Across courses, the authors reflected on increased student engagement when digital tools were used not simply for task completion but to support inquiry, discourse, and authentic creation for real audiences.
Keywords: Comprehension; Computer science; Critical thinking; Digital literacy; Disengagement theory; Linguistics; Literacy; Mathematics education; Pedagogy; Psychology; Reading (process); Reading comprehension; Sociology; Student engagement; Task (project management); dept.cur

“I’m like white people here”: Chinese international doctoral students’ perception of ethno-racial issues in China (poster 23) - Wang, Peiwen (AERA 2025 Annual Conference, 2025)
Keywords: China; Law; Media studies; Perception; Political science; Psychology; Sociology; White (mutation); dept.cur

The failures and possibilities of philosophy in the material world - Van Cleave, Jessica; Marn, Travis; Wolgemuth, Jennifer (International Review of Qualitative Research, 2025)
Keywords: Engineering; Engineering ethics; Epistemology; Philosophy; dept.cur

Manufacturing Trustworthiness in Qualitative Research as a Writerly and Readerly Accomplishment: Introduction to the Special Issue - Van Cleave, Jessica; Wolgemuth, Jennifer; Marn, Travis (Qualitative Inquiry, 2025)
Keywords: Construct (python library); Product (mathematics); Qualitative research; Space (punctuation); Theme (computing); Tinker; Trustworthiness; dept.cur; possibility; publication; scholarly writing; trustworthiness

Producing Participants: Trustworthiness as Convenient Fiction - Van Cleave, Jessica; Marn, Travis (Qualitative Inquiry, 2025)
Keywords: Objectivity (philosophy); Qualitative research; Quality (philosophy); Reputation; Rigour; Transparency (behavior); Trustworthiness; Verisimilitude; dept.cur; fiction; methodologies; qualitative criteria; qualitative research; transparency; trustworthiness

#scholar #famous #monster - Wolgemuth, Jennifer; Lester, Jessica; Guyotte, Kelly; Koro‐Ljungberg, Mirka; Marn, Travis (Educational Researcher, 2025)
Academic success is now coupled with social media engagement. Social media has become so normalized in the academy that absent a carefully curated social media presence, scholars risk being seen as unscholarly, unproductive, and unpopular. This article lays bare the pressures, mechanisms, and monstrosities of using social media to promote scholarship. We argue that the widespread adoption of social media outpaces critical attention to its ethics and wonder about the future of public scholarship and the monstrous scholarly selves we are becoming. Thinking of monstrosity, with Krecˇicˇ and Žižek, as the preontological domain that rests beneath society and constitutes alterity and otherness, we ask what kinds of #scholarfamousmonsters we want to be, become, and promote in the digital era.
Keywords: Aesthetics; Art; Epistemology; Law; Literature; Media studies; Monster; Philosophy; Political science; Psychology; Scholarship; Social media; Social psychology; Sociology; Wonder; dept.cur; peer-reviewed

Elementary preservice teachers' use of the crosscutting concepts to plan NGSS ‐aligned science lessons in explicit versus non‐explicit contexts - Sherwood, Carrie‐Anne; Benedict‐Chambers, Amanda (School Science and Mathematics, 2025)
Keywords: Context (archaeology); Discipline; Lesson plan; Mathematics; Mathematics education; Next Generation Science Standards; Pedagogy; Plan (archaeology); Psychology; Science education; Significant difference; Sociology; dept.cur; peer-reviewed